Langkah Strategis Pembinaan Umat Oleh Penyuluh Agama Hindu Di Masa Pandemi - Duwi Oktaviana; I Kadek Abdhi Yasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Now adays, human life is greatly influenced by technological developments and advances. The negative impact of technological developments needs to be addressed immediately so as not to have a negative impact on society, especially the younger generation. These countermeasures need to involve relevant stakeholders. The Hindu religious guide is one of the many translators who convey messages to the public. The role of a religious educator is getting heavier from day to day. This is because the irregularities that occur in society are also increasing day by day. It needs to be underlined, the task of Hindu extension workers has gotten heavier since the Covid-19 outbreak. The outbreaks that hit the world, especially Indonesia in the last six months, have caused many losses. This is what makes Hindu religious instructors have to carry out other strategies so that their task in providing dharma enlightenment to the community continues. There are strategic steps that can be taken, namely: making videos containing dharma messages and conducting counseling to the target villages. Making videos includes: collecting guidance and counseling materials, compiling written concepts of extension material in the form of scripts, and making videos of cultural arts performances or performing arts as actors and supporters of discourse. Meanwhile, counseling to assisted villages can be done by: conducting interactive dialogues, compiling operational work plans, and drafting the concept of extension material in the form of posters with Hindu religious props.Keywords: Hindu development, Hindu religious counselor